About TreeTorika: Rhetoric, CAAC and Mao - Lindborg, PerMagnus (Editions Delatour France, 2016)
This chapter examines computer assisted analysis and composition (CAAC) techniques in relation to the composition of my piece TreeTorika for chamber orchestra. I describe methods for analysing the musical features of a recording of a speech by Mao Zedong, in order to extract compositional material such as global form, melody, harmony and rhythm, and for developing rhythmic material. The first part focuses on large-scale segmentation, melody transcription, quantification and quantization. Automatic tran- scription of the voice was discarded in favour of an aural method using tools in Amadeus and Max/MSP. The data were processed in OpenMusic to optimise the accuracy and readability of the notation. The harmonic context was derived from the transcribed melody and from AudioSculpt partial tracking and chord sequence analyses. The second part of this chapter describes one aspect of computer assisted composition, that is the use of the rhythm constraint library in OpenMusic to develop polyrhythmic textures. The flexibility of these techniques allowed the computer to assist me in all but the final phases of the work. In addition, attention is given to the artistic and political implications of using recordings of such a disputed public figure as Mao.